СТАН ФІНАНСОВОГО ЗАБЕЗПЕЧЕННЯ ГАЛУЗІ ОХОРОНИ ЗДОРОВ'Я В УКРАЇНІ - Пархета, Людмила Віталіївна (Науковий журнал «Світ фінансів», 2018)
Пархета Л. В. Стан фінансового забезпечення галузі охорони здоров’я в Україні. Проаналізовано сучасний стан фінансування охорони здоров'я в Україні та його вплив на забезпечення населення медичними послугами на достатньому рівні й належної якості. Розглянуто джерела фінансового забезпечення системи охорони здоров’я України та їх структуру. Зазначено, що фінансове забезпечення охорони здоров’я на державному рівні є вкрай недостатнім і таким, що не забезпечує у повному обсязі конституційних прав громадян на отримання медичної допомоги. Визначено, що ці проблеми багато в чому вирішуються за умови розвитку страхової медицини, яка забезпечує не тільки можливість отримати належну медичну допомогу, а й передбачає здійснення дієвого контролю з боку страхових організацій за раціональним використанням фінансовихресурсів сфери охорони здоров’я. Пархета Л. В. Состояние финансового обеспечения здравоохранения в Украине. Проанализировано современное состояние финансирования здравоохранения в Украине и его влияние на обеспечение населения медицинскими услугами на достаточном уровне и надлежащего качества. Рассмотрены источники финансового обеспечения системы здравоохранения Украины и их структуру. Отмечено, что финансовое обеспечение здравоохранения на государственном уровне является крайне недостаточным и не обеспечивающим в полном объеме конституционных прав граждан на получение медицинской помощи. Определено, что эти проблемы во многом решаются за счет развития страховой медицины, которая обеспечивает не только возможность получить надлежащую медицинскую помощь, но и предусматривает осуществление действенного контроля со стороны страховых организаций за рациональным использованием финансовых ресурсов здравоохранения. Parkheta L. The state offinancial securityofthe healthcare sectorin Ukraine. Introduction. Organization ofeffective functioning and development ofhealth care system in the conditions of limited financial resources is the most important task ofthe authorities at all levels. Therefore, the question ofassessing the current state ofhealth and identifying the main problems of financing health care institutions relevant is more than ever.Purpose. The purpose of the article is to analyze the current state of financial securement ofhealth care in Ukraine. To identify the main problems ofthe development ofthe health sector and to develop recommendations for improving existing and finding new sources of financial support forthe health care system.Results. The results of the analysis show that in recent years, despite an annual increase in health care expenditures, their share in the budget structure is reduced by redistribution to finance other activities ofthe state. The financial support ofhealth care at the state level is extremely insufficient. Apart from the problem of financing health expenditures, attention is drawn to the problem of inefficient and inappropriate use of available resources by the network ofhealth care facilities, which in many cases does not correspond to the real needs ofthe population.Conclusion. It is concluded that the problems of financing health care are largely solved by the introduction of insurance medicine, which ensures not only the ability to receive proper medical care by the population of Ukraine, but also provides effective control by insurance organizations to the rational use of financial resources of the health care sector.